MAPPING ENGLISH SKILLS REQUIRED FOR TEACHING PHYSICS IN BILINGUAL CLASROOMS: A SURVEY - Wihdah Dwi Fathani; Salsabila Naylah Safitri; Wahyunengsih Wahyunengsih (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2026)
This study aims to identify the English language skills required for effective physics teaching in bilingual classrooms and to address the limited evidence on how English proficiency supports content delivery in Indonesian EMI settings. There is a gap between teachers' language preparedness and the demands of the classroom since many teachers still struggle with both receptive and productive abilities, despite the fact that English is being used as a medium of instruction more and more. A descriptive quantitative survey was employed, involving 51 physics teachers and pre-service teachers who completed a 40-item Likert scale questionnaire measuring listening, speaking, reading, writing, and professional development needs related to bilingual instruction. The findings show that writing had the lowest mean score (3.46), while listening had the highest mean score (3.75), followed by reading (3.74) and speaking (3.58). These results imply that in bilingual physics classrooms, receptive skills take precedence over productive skills. The study finds that in order to boost teachers' confidence and classroom efficacy in EMI-based instruction, teacher education programs should integrate English language development with physics pedagogy and build listening and reading competencies.